ESTIMATION OF MAXIMUM WAVE CHARACTERISTICS IN THE VAN PHONG BAY AREA, KHANH HOA PROVINCE - Mau, Le Dinh (Vietnam Journal of Marine Science and Technology, 2007)
Estimation of maximum wave characteristics in a particular nearshore area have an important role of economic, tourism developments and environmental protection such as design of marine structures, transportation, fisheries and mari-culture, recreation, etc., for sustainable exploitation of the coastal zone. This paper presents the distribution of calculated wave characteristics in the Van Phong bay area for typical maximum wind fields, which were taken from Nha Trang Meteorological Station during 1986 to 2000. Typical Tubong wind fields were taken from the investigation report of the Mete-Hydrological Service in Nha Trang. Dolphin and SWAN models estimated wave characteristics in the offshore and nearshore regions, respectively. Study results show that the Van Phong bay area was strongest affected by wave action in case of maximum incoming winds in the sector from NW to E directions, and slightly affected by the remaining incoming wind directions. Maximum wind field (V = 28 m/s, Direction = NE) genemted significant wave height of greater than 2 m which covered the most parts of Van Phong bay area, the coastline from Hon Khoi Cape to Ban Thang Cape was subjected to wave action with significant wave height of 3 - 6 m. Typical Tubong windfield (V = 20 m/s. Direction = NW) genemted significant wave height of 0.5 - 1.5 m Ben Goi and 1.5 - 2.5 m in Van Phong bay areas.